Notch controls cell adhesion in the Drosophila eye. - Sujin Bao (PLoS Genetics, 2014)
Sporadic evidence suggests Notch is involved in cell adhesion. However, the underlying mechanism is unknown. Here I have investigated an epithelial remodeling process in the Drosophila eye in which two primary pigment cells (PPCs) with a characteristic 'kidney' shape enwrap and eventually isolate a group of cone cells from inter-ommatidial cells (IOCs). This paper shows that in the developing Drosophila eye the ligand Delta was transcribed in cone cells and Notch was activated in the adjacent PPC precursors. In the absence of Notch, emerging PPCs failed to enwrap cone cells, and hibris (hbs) and sns, two genes coding for adhesion molecules of the Nephrin group that mediate preferential adhesion, were not transcribed in PPC precursors. Conversely, activation of Notch in single IOCs led to ectopic expression of hbs and sns. By contrast, in a single IOC that normally transcribes rst, a gene coding for an adhesion molecule of the Neph1 group that binds Hbs and Sns, activation of Notch led to a loss of rst transcription. In addition, in a Notch mutant where two emerging PPCs failed to enwrap cone cells, expression of hbs in PPC precursors restored the ability of these cells to surround cone cells. Further, expression of hbs or rst in a single rst- or hbs-expressing cell, respectively, led to removal of the counterpart from the membrane within the same cell through cis-interaction and forced expression of Rst in all hbs-expressing PPCs strongly disrupted the remodeling process. Finally, a loss of both hbs and sns in single PPC precursors led to constriction of the apical surface that compromised the 'kidney' shape of PPCs. Taken together, these results indicate that cone cells utilize Notch signaling to instruct neighboring PPC precursors to surround them and Notch controls the remodeling process by differentially regulating four adhesion genes.